Future time perspective, procrastination and academic motivation in argentinian college students during the pandemic - Brenlla, María Elena (2022)
Fil: Brenlla, María Elena. Pontificia Universidad Católica Argentina. Facultad de Psicología y Psicopedagogía. Centro de Investigación en Psicología y Psicopedagogía; Argentina